Algeria : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on Algeria reports that the authorities have relied on an expansionary fiscal stance to stimulate growth and employment, but structural reforms have virtually stalled. Although the economy has recorded increasing growth, the nonhydrocarbon sector remains small and unemployment pervasive. The current political stability and a strong financial position provide a favorable framework for taking decisive steps to strengthen private sector activities and to complete the transition to a market economy.